Revitalizing Kaba Sabai Nan Aluih Through The Transfer of Animated Films and Other Creative Media - Ninawati Syahrul; Sastri Sunarti; Atisah Atisah (Universitas Sebelas Maret, 2022)
Kaba or Minang oral literature is slowly being pushed aside by the rapid development of the times. Therefore, we need an action for preservation, namely by transferring the vehicle. One of the kaba entitled Kaba Sabai nan Aluih contains moral values, religious values, and cultural values. The transfer of Wahana Kaba Sabai nan Aluih is an opportunity as well as a strategy to maintain the cultural heritage of kaba or oral literature in the era of technological disruption. The transfer of the vehicle is also so that the ancestral heritage in the form of kaba is not lost and the value contained in it can still be conveyed to the next generation of the nation. This study aims to reveal the use of information technology, especially in making the script of Kaba Sabai nan Aluih in the form of animated films and other creative media. This research uses the perspective of the transfer theory theory. The data is sourced from literature studies or narrative texts in articles, books, and journals related to the transfer of vehicles. The method used in this study is a qualitative descriptive method. This study shows that the conversion of the kaba into animated films or other creative media can prolong the life of the kaba in society. In addition, to introduce the younger generation to the typical kaba from the Minang area, West Sumatra. In adapting kaba into an animated film requires a touch of technology. Through technology, kaba can be adapted by bringing the perspective of the nation's next generation closer, namely in the form of animated films. The concept of transfer of vehicle is only a bridge in order to be able to pass on the value of the past into the value of the present in a way that is acceptable, digestible, and more attractive to the current generation. The transfer of the vehicle is just an effort to adapt to the context of the times and the interests of the younger generation. Therefore, the more attractive media is technology-based or digital multimodal media. However, the orientation of the child is still led to the book. As long as it has a mature concept, collaboration from the creative media industry, and sufficient funding, the animation can be accepted by the community so that kaba or oral literature is well protected and continues to live in society even though it is in a different world.